Combined administration of laminin-221 and prostacyclin agonist enhances endogenous cardiac repair in an acute infarct rat heart - Nagako Sougawa (Nature Portfolio, 2021)
Abstract Although endogenous cardiac repair by recruitment of stem cells may serve as a therapeutic approach to healing a damaged heart, how to effectively enhance the migration of stem cells to the damaged heart is unclear. Here, we examined whether the combined administration of prostacyclin agonist (ONO1301), a multiple-cytokine inducer, and stem cell niche laminin-221 (LM221), enhances regeneration through endogenous cardiac repair. We administered ONO1301- and LM221-immersed sheets, LM221-immersed sheets, ONO1301-immersed sheets, and PBS-immersed sheets (control) to an acute infarction rat model. Four weeks later, cardiac function, histology, and cytokine expression were analysed. The combined administration of LM221 and ONO1301 upregulated angiogenic and chemotactic factors in the myocardium after 4 weeks and enhanced the accumulation of ILB4 positive cells, SMA positive cells, and platelet-derived growth factor receptor alpha (PDGFRα) and CD90 double-positive cells, leading to the generation of mature microvascular networks. Interstitial fibrosis reduced and functional recovery was prominent in LM221- and ONO1301-administrated hearts as compared with those in ONO1301-administrated or control hearts. LM221 and ONO1301 combination enhanced recruitment of PDGFRα and CD90 double-positive cells, maturation of vessels, and functional recovery in rat acute myocardial infarction hearts, highlighting a new promising acellular approach for the failed heart.